Citizenship as cultural: Towards a theory of cultural citizenship. Issue 10 (October 2016) - Beaman, Jean
Abstract: Traditional notions of citizenship have focused on formal membership, including access to rights, in a national community. More recent scholarship has expanded this definition beyond citizenship as a legal status to focus on struggles for societal inclusion of and justice for marginalized populations, citizenship as both a social and symbolic boundary of exclusion, and post‐colonial and post‐national citizenship. In this article, I review conceptions of citizenship that involve more than legal rights. After reviewing this scholarship, I discuss the theoretical framework of cultural citizenship – a move to center the cultural underpinnings of modern citizenship in analyses of citizenship as a boundary of inclusion and exclusion. I use the example of France as one site to locate the connections between citizenship and culture and the cultural underpinnings and implications of citizenship more broadly.